Virtual Community Strategy Adventure Towards Something In Presenting Campaign Messages Through Instagram Accounts - Sugiyo Winoto; Marwan Marwan; Retno Dhamayanti (Dinasti International Journal of Education Management And Social Science, 2024)
This research aims to explain the campaign content raised by the Adventure Towards Something Virtual Community via its Instagram account@adventure towards something; describe the strategy of the Adventure Towards Something Virtual Community in presenting campaign messages via Instagram accounts; and describes the responses of community participants regarding the campaign carried out by the Adventure Towards Something Virtual Community via their Instagram account@adventure towards something. This research uses qualitative methods with a netnographic study approach. The selection of informants in this research was carried out using purposive sampling. The data analysis technique in this research goes through the stages of coding, noting, abstracting and comparing, checking and refinement, generalizing, and theorizing. The results of the research consist of three things, first, the digital comic Adventure to Something (PMS) has types and variations in content sharing which are wrapped in social media hashtag practices. Second, to present this content, PMS uses message strategies and media strategies that generate social connections from online connections through close social networks consisting of interconnected people with very few participants. Third, community participants consume sign-value and symbolic-value from Instagram features and merchandise products that help them discover, know, follow, and find meaning from PMS content to grow connections. social from online connections in relationships between "Seekers" and co-creators.